Morphometric study and watershed prioritization for soil conservation in Kalinjar micro-watersheds, Odisha - Sajal Barh (National Geographical Journal of India, 2023)
The detailed study of morphometry is very important to understand the hydrological comportment and characteristics of the watershed. The morphometric parameters are used for prioritization of the micro-watersheds based on WSA (weighted sum analysis) for sustainable watershed management. In this study, a collective approach of using remotely sensed DEM, topographical map and ArcGIS (10.1) has been applied to define morphometric parameters of the Kalinjar river basin, a sub-basin of Baitarani River which is prone to gully erosion. Seven micro-watersheds of Kalinjar River have been prioritized by applying the morphometric parameters and ranking them according to their liability to soil erosion. According to results, Kalinjar River is a 6th order stream having four 5th order and one 6th order sub-watershed, having a total drainage area of 506.34 km². High values of infiltration number are indicative of low infiltration which may cause high surface runoff and soil erosion. The micro-watershed prioritization implied that MW-4 (16.79% area) is an extremely vulnerable micro-watershed that requires better attention for soil and water conservation measures. The result of the prioritization shows that micro-watersheds MW-1 and MW-3 (13.33% area) are the most vulnerable micro-watersheds to erosion, micro-watersheds MW-2 and MW-5 (13.97% area) are moderately vulnerable and micro-watersheds MW-6 and MW-7 (23.16% area) are the least vulnerable to erosion.